2021
DOI: 10.1166/sam.2021.3957
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Migration Characteristics of Fluorine in Ash-Sluicing Water in Soils

Abstract: The excessive fluorine content in ash-sluicing water has become one of the main environmental pollution problems in the thermal power generation industry. This study selected 5 representative soil types and used fluoride ions (F-) as the pollution control factor. The experimental results showed that the isotherms of the F- solutions prepared by deionized water (adsorbed by Jianbi clay and Fengrun sandy soil) and ash-sluicing water all conformed to the Langmuir isothermal adsorption equation. In terms of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The chief water contaminants are households, organic materials, drug manufacturers, large-scale animal feeding operations, organic materials, industries, and pharmaceutical residues [ 4 , 5 , 6 ]. Notably, the World Health Organization revealed that nearly 30% of individuals living rurally need hygienic water sources, and more than 2,000,000 humans die every year from contamination of drinkable water [ 7 , 8 , 9 ]. Among the different pollutants, the most notorious are pharmaceutical residues, which harm biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…The chief water contaminants are households, organic materials, drug manufacturers, large-scale animal feeding operations, organic materials, industries, and pharmaceutical residues [ 4 , 5 , 6 ]. Notably, the World Health Organization revealed that nearly 30% of individuals living rurally need hygienic water sources, and more than 2,000,000 humans die every year from contamination of drinkable water [ 7 , 8 , 9 ]. Among the different pollutants, the most notorious are pharmaceutical residues, which harm biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…solidifiers, absorbents, dispersants, booms, and skimmers have been employed for the adsorption of organic solvents from water/soil bodies [ 8 , 9 , 10 , 11 ]. With the exception of absorbents, all of these methods have some drawbacks, including low recovery rate, secondary contamination, higher time consumption, and non-biodegradable in nature [ 12 , 13 , 14 , 15 ]. These days, the main focus is on absorbent substances, as they effectively trap organic solvents from the polluted spill site [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%